APOE Genotypes, Lipid Profiles, and Associated Clinical Markers in a Finnish Population with Cardiovascular Disease Risk Factor - Leskinen Heidi; Tringham Maaria; Karjalainen Heli; Iso-Touru Terhi; Hietaranta-Luoma Hanna-Leena; Marnila Pertti; Pihlava Juha-Matti; Hurme Timo; Puolijoki Hannu; Åkerman Kari; Mäkinen Sari; Sandell Mari; et al. (Karger, 2022)
Introduction: The APOE ε4 allele predisposes to high cholesterol and increases the risk for lifestyle-related diseases such as Alzheimer's disease and cardiovascular diseases (CVDs). The aim of this study was to analyse interrelationships of APOE genotypes with lipid metabolism and lifestyle factors in middle-aged Finns among whom the CVD risk factors are common.
Methods: Participants (n = 211) were analysed for APOE ε genotypes, physiological parameters, and health- and diet-related plasma markers. Lifestyle choices were determined by a questionnaire.
Results: APOE genotypes ε3/ε4 and ε4/ε4 (ε4 group) represented 34.1% of the participants. Genotype ε3/ε3 (ε3 group) frequency was 54.5%. Carriers of ε2 (ε2 group; ε2/ε2, ε2/ε3 and ε2/ε4) represented 11.4%; 1.9% were of the genotype ε2/ε4. LDL and total cholesterol levels were lower (p < 0.05) in the ε2 carriers than in the ε3 or ε4 groups, while the ε3 and ε4 groups did not differ. Proportions of plasma saturated fatty acids (SFAs) were higher (p < 0.01), and omega-6 fatty acids lower (p = 0.01) in the ε2 carriers compared with the ε4 group. The ε2 carriers had a higher (p < 0.05) percentage of 22:4n-6 and 22:5n-6 and a lower (p < 0.05) percentage of 24:5n-3 and 24:6n-3 than individuals without the ε2 allele.
Conclusions: The plasma fatty-acid profiles in the ε2 group were characterized by higher SFA and lower omega-6 fatty-acid proportions. Their lower cholesterol values indicated a lower risk for CVD compared with the ε4 group. A novel finding was that the ε2 carriers had different proportions of 22:4n-6, 22:5n-6, 24:5n-3, and 24:6n-3 than individuals without the ε2 allele. The significance of the differences in fatty-acid composition remains to be studied.